Corruption and Anti-Corruption - Larmour, Peter (ANU Press, 2013)
There is new international attention being given to the old problem of corruption. It has been taken up by international organisations, and driven by economic analysis. It is impatient of cultural justifications, and suspicious of state action. It is concerned with corruption prevention as much as detection, investigation and prosecution. Corruption and Anti-Corruption deals with the international dimensions of corruption, including campaigns to recover the assets of former dictators, and the links between corruption, transnational and economic crime. It deals with corruption as an issue in political theory, and shows how it can be addressed in campaigns for human rights. It also presents case studies of reform efforts in Philippines, India and Thailand. The book explains the doctrines of a well-established domestic anticorruption agency. It is based on research to develop a curriculum for a unique international training course on 'Corruption and Anti-Corruption', designed and taught by academics at The Australian National University, the Australian Institute of Criminology and public servants in the New South Wales Independent Commission Against Corruption. Versions have been taught in Canberra, and several countries in South East Asia.